Tool to integrate and measure gender equality in monitoring and evaluation of climate services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
This tool is the result of a review of literature as well as impact assessment of three CCAFS-supported projects. The next stages involve use of the framework/tool to measure gender results.